Development and validation of a rapid LC‐MS/MS method for the detection of 182 novel psychoactive substances in whole blood. Issue 2 (21st October 2021) - Giorgetti, Arianna; Barone, Rossella; Pelletti, Guido; Garagnani, Marco; Pascali, Jennifer; Haschimi, Belal; Auwärter, Volker
Abstract: Introduction: The analysis of novel psychoactive substances (NPS) represents a challenge in forensic toxicology, due to the high number of compounds characterized by different structures and physicochemical properties both among different subclasses and within a single subclass of NPS. The aim of the present work is the development and validation of a targeted liquid chromatography tandem mass spectrometry (LC‐MS/MS) method for the detection of NPS in whole blood. Materials and methods: A protein‐precipitation based LC‐MS/MS method for the detection of more than 180 NPS was developed and validated by assessing the following parameters: selectivity, linearity, accuracy, precision, limit of detection (LOD) and of quantification (LOQ) recovery, and matrix effect. Then, the method was applied to real forensic samples. Results: The method allowed the identification of 132 synthetic cannabinoids, 22 synthetic opioids, and 28 substances among synthetic cathinones, stimulants, and other drugs. Validation was successfully achieved for most of the compounds. Linearity was in the range of 0.25–10 ng/ml for synthetic cannabinoids and 0.25–25 ng/ml for other drugs. Accuracy and precision were acceptable according to international guidelines. Three cases tested positive for fentanyl and ketamine, in the setting of emergency room administration. Conclusions: The present methodology represents a fast, not expensive, wide‐panel method for the analysis of more than 180 NPS by LC‐MS/MS, which can be profitably applied both in a clinical context and in postmortem toxicology. Abstract : The study provides a method for the detection of more than 180 NPS pertaining to different subclasses.